When heroes love : the ambiguity of eros in the stories of Gilgamesh and David - Ackerman, Susan (Gender, theory, and religion., 2005)
Toward the end of the Mesopotamian Epic of Gilgamesh King Gilgamesh laments the untimely death of his comrade Enkidu, "my friend whom I loved dearly." Similarly in the Bible, David mourns his companion, Jonathan, whose "love to me was wonderful, greater than the love of women." These passages, along with other ambiguous erotic and sexual language found in the Gilgamesh epic and the biblical David story, have become the object of numerous and competing scholarly inquiries into the sexual nature of the heroes' relationships. Susan Ackerman's innovative work carefully examines the stories' sexual and homoerotic language and suggests that its ambiguity provides new ways of understanding ideas of gender and sexuality in the ancient Near East and its literature.